Between heritage and plan: argumentative study on Paranaguá, Paraná (Tempo e Argumento, 2022)
Since the second half of the twentieth century, the heritage listing has persisted as the main alternative for safeguarding cultural assets in Brazil, while from the 2000s onwards, the municipal masterplan establishes protective guidelines for remaining areas of the evolutionary narrative of contemporary cities. In view of these assertions, the general objective of the research is to analyze arguments related to the protection of the memory of the historic center of Paranaguá, Paraná. With an exploratory feature and a qualitative approach, the investigation was supported by techniques of the literature revision and by documentary analyzes. Their results indicate that heritage policy tool and the aforementioned urban planning instrument contribute to both positive changes and adverse externalities, with risks to the cognition of the past in the present and its respective transmissibility to the future. By interpreting the historical and empirical issues of the case study, it can also be deduced that the effectiveness of these actions depends on the recognition of the values and meanings of individual and collective heritage. Finally, it follows that, as a consequence of mismatches of thought between different instances - public and private, humanity's legacies are left adrift and susceptible to irreversible losses and the complete or partial vanishing of the history of local communities.
Keywords: historical centers; patrimonial goods; urban planning; present tense